Desarrollo de habilidades de pensamiento científico: una estrategia didáctica para niños de la zona altos de Cazucá con el propósito de aproximarlos a la noción de temperatura - Quijano Urrego, Stefanny Jahel; Malagón, Rusby Yalile; Bautista, Germán (Revista Científica, 2011)
This work evolves from our intervention at the institution “Corporación Social Fé y Esperanza” at Bogota, Colombia. This work has been an opportunity to reflect on the harsh context the children has to endure due to their condition of being displaced from their home land. We aim to put forward a didactical strategy to improve the development of scientific thinking’s skills by approaching them to de concept of temperature. In this strategy we set up contexts in which the students develop their ability to make question, to observe events, to realize description and to explain some natural phenomena of their environment. It is an option to see an design new ways to present science to children belonging to this contexts, by stimulating their taste to inquire and research on what happen in their surroundings, as well.